2011
DOI: 10.1111/j.1365-2044.2011.06648.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of combining dexamethasone with ondansetron for nausea and vomiting associated with fentanyl‐based intravenous patient‐controlled analgesia*

Abstract: SummaryWe investigated whether combined dexamethasone and ondansetron is more effective than ondansetron alone in preventing postoperative nausea and vomiting in patients with fentanyl-based intravenous patient-controlled analgesia. One hundred and thirty patients undergoing videoassisted thoracoscopic surgery were assigned to either an ondansetron group or a dexamethasone and ondansetron group. In all patients, ondansetron 4 mg was administered at the end of surgery and 12 mg was added to the patient-controll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 29 publications
1
27
1
Order By: Relevance
“…Neither postoperative pain nor the amounts of rescue analgesics used differed among the groups in this study. Although several clinical trials have shown that a single perioperative use of dexamethasone 8 mg significantly reduced postoperative pain scores and analgesic requirements in patients who underwent LC [21,22], we did not observe an analgesic effect with dexamethasone alone compared to ramosetron alone [13,23]. A single dose of dexamethasone administered perioperatively is rarely associated with significant side effects such as increased risk of infection, glucose intolerance, delayed wound healing, and adrenal suppression [24].…”
Section: Discussioncontrasting
confidence: 62%
“…Neither postoperative pain nor the amounts of rescue analgesics used differed among the groups in this study. Although several clinical trials have shown that a single perioperative use of dexamethasone 8 mg significantly reduced postoperative pain scores and analgesic requirements in patients who underwent LC [21,22], we did not observe an analgesic effect with dexamethasone alone compared to ramosetron alone [13,23]. A single dose of dexamethasone administered perioperatively is rarely associated with significant side effects such as increased risk of infection, glucose intolerance, delayed wound healing, and adrenal suppression [24].…”
Section: Discussioncontrasting
confidence: 62%
“…A previous study clarified the effectiveness of steroids for prevention of opioid-induced nausea. 19,20 Treatment with steroids often results in increased appetite, reduced nausea and improved well-being in patients with advanced metastatic cancer. 21 It might also be better to use steroid as prophylactic medication for prevention of opioid-induced nausea for patients with risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…As an antiemetic agent, it has been used at a dose ranging between 2.5-10 mg/day 19,20 . Since nausea and vomiting can occur by a variety of different mechanisms, combinations of different antiemetics are used to prevent or treat these symptoms 6,21 . By the help of these combinations, multiple routes that can lead to nausea and vomiting can be blocked 22 .…”
Section: Introductionmentioning
confidence: 99%